Landmines and Unexploded Ordnance : A Resource Book - McGrath, Rae (London Pluto Press, 2000)
A study of landmines in the post-conflict situation. Provides data on all aspects of landmining and the moves for its abolition. McGrath provides an introduction to landmines, a discussion on necessary education and rehabilitation and advice for people working in or visiting affected areas. Aimed at people involved in the anti-landmine campaign.
Include Glossary and Index
Keywords: Ammunition -- Bombs -- Land Mines--Economic Aspects -- Land Mines--Social Aspects